Impact of cover crops and termination timing on weed management in corn - Vipin Kumar; Vijay Singh; Michael L. Flessner; Mark S. Reiter; Annu Kumari; Andrew Price; Thomas P. Kuhar; Steven B. Mirsky (Weed Technology)
This study evaluated the impact of four cover crop species and their termination timings on cover crop biomass, weed control, and corn yield. A field experiment was arranged in a split-plot design in which cover crop species (wheat, cereal rye, hairy vetch, and rapeseed) were the main plot factor, and termination timings [4, 2, 1, and 0 wk before planting corn (WBP)] was the subplot factor. In both years (2021 and 2022), hairy vetch produced the most biomass (5,021 kg ha–1) among cover crop species, followed by cereal rye (4,387 kg ha–1), wheat (3,876 kg ha–1), and rapeseed (2,575 kg ha–1). Regression analysis of cover crop biomass with accumulated growing degree days (AGDDs) indicated that for every 100 AGDD increase, the biomass of cereal rye, wheat, hairy vetch, and rapeseed increased by 880, 670, 780, and 620 kg ha–1, respectively. The density of grass and small-seeded broadleaf (SSB) weeds at 4 wk after preemergence herbicide (WAPR) application varied significantly across termination timings. The grass and SSB weed densities were 56% and 36% less at 0 WBP compared with 2 WBP, and 67% and 61% less compared with 4 WBP. The sole use of a roller-crimper did not affect the termination of rapeseed at 0 WBP and resulted in the least corn yield (3,046 kg ha–1), whereas several different combinations of cover crops and termination timings resulted in greater corn yield. In conclusion, allowing cover crops to grow longer in the spring offers more biomass for weed suppression and impacts corn yield.